Atomistic investigation of mechanical behavior for CNT reinforced nanocrystalline aluminum under biaxial tensile loading. (2020) - Babu, Pokula Narendra; Gargeya, B.S.K.; Ray, Bankim Chandra; Pal, Snehanshu
Abstract: In this paper, the mechanical behavior of nanocrystalline aluminum and carbon nanotube reinforced NC Al composites have been examined by using molecular dynamics simulations under biaxial tensile loading. Armchair type of (5, 5) CNT, (15, 15) CNT, (30, 30) CNT and three different temperatures (10 K, 300 K and 681 K) have been considered to perform tensile test at a strain rate of 10 9 s −1 . CNT reinforced NC Al composites have exhibited diminished in ultimate tensile strengths and fracture strains compared to NC Al without CNT specimen, corresponding to simulated temperatures. On the other hand, only (15, 15) CNT incorporated NC Al specimen exhibited higher fracture strain in contrast to NC Al specimen at room temperature in which load bearing capacity of composite has been enriched through CNT. The thermal fluctuations have increased with increase in temperature and which leads to reduce in mechanical properties. Dislocation density analysis and Centrosymmetry parameter analysis have been carried out to evaluate the structure evolution of the composites at different strains during biaxial tensile loading. The deformation behavior of NC Al and CNT reinforced NC Al composites have been analysed at various temperatures with respect to three different CNT diameters.